2021
DOI: 10.3201/eid2707.203948
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Aerosol Exhaled by Experimentally Infected Cynomolgus Monkeys

Abstract: https://www.wsj.com/articles/ u-k-delays-second-covid-19-vaccine-dose-as-europeponders-how-to-speed-up-immunization-11609334172 8. US Food and Drug Administration. FDA statement on following the authorized dosing schedules for COVID-19 vaccines. January 4, 2021 [cited 2021 Jan 14]. https://www. fda.gov/news-events/press-announcements/fda-statementfollowing-authorized-dosing-schedules-covid-19-vaccines 9. Livingston EH. Necessity of 2 doses of the Pfizer and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
5
15
0
Order By: Relevance
“…One previous study has been unable to culture virus in exhaled breath from COVID-19 patients ( 26 ), which could be due to unknown or late collection times postonset of disease. Another study was unable to culture virus from aerosol particles collected from nonhuman primates ( 17 ), possibly due to reliance on equipment and buffers that do not maintain viral infectivity. Our results support the idea that transmission is likely to occur prior to or concurrent with symptom onset or in the absence of severe clinical disease, supporting studies that have found that asymptomatic infection is a major driver of community transmission ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study has been unable to culture virus in exhaled breath from COVID-19 patients ( 26 ), which could be due to unknown or late collection times postonset of disease. Another study was unable to culture virus from aerosol particles collected from nonhuman primates ( 17 ), possibly due to reliance on equipment and buffers that do not maintain viral infectivity. Our results support the idea that transmission is likely to occur prior to or concurrent with symptom onset or in the absence of severe clinical disease, supporting studies that have found that asymptomatic infection is a major driver of community transmission ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…For COVID-19 patients, SARS-CoV-2 RNA was detected in exhaled breath ( 14 , 15 ). In nonhuman primates, SARS-CoV-2 RNA has also been detected in aerosol particles collected from inoculated animals ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 77 ] demonstrated that CMs experimentally infected with SARS-CoV-2 exhaled aerosol-size particles containing SARS-CoV-2, with peak shedding occurring at 2 DPI; the average exhaled load was 106 viral RNA-containing particles min −1 ; the size distribution was measured and revealed a distribution of 27.4%, 49.6% and 23.0% in the size fractions 0.65–2.1 µm, 2.1–4.7 µm and greater than 4.7 µm, respectively. Attempts at isolation in cell culture were unsuccessful.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Our studies support reports of infectious SARS-CoV-2 collected from aerosols near COVID-19 patients [4][5][6][7], as well as studies showing non-contact transmission of SARS-CoV-2 between ferrets and hamsters [17,18,22], including one study that demonstrated transmission over a 1-meter distance [28]. Some previous studies have been unable to culture virus from air samples from COVID-19 patients or inoculated non-human primates due to unknown collection times post-onset of disease or the use of air sampling equipment or buffers that do not maintain viral infectivity [16,29]. Our results support the idea that transmission is likely to occur prior to or concurrent with symptom onset or in the absence of clinical disease, supporting studies that have found that asymptomatic infection is a major driver of community transmission [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…For COVID-19 patients, the emission rate of SARS-CoV-2 RNA in EBC was estimated to be >1 million viral RNA copies/hour by breathing [13,14]. In non-human primates, SARS-CoV-2 RNA has also been detected in EBC collected from inoculated animals [15,16].…”
Section: Introductionmentioning
confidence: 99%